If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5) * 2 + -1(x + 5)(x + -5) = 0 Reorder the terms: (5 + x) * 2 + -1(x + 5)(x + -5) = 0 Reorder the terms for easier multiplication: 2(5 + x) + -1(x + 5)(x + -5) = 0 (5 * 2 + x * 2) + -1(x + 5)(x + -5) = 0 (10 + 2x) + -1(x + 5)(x + -5) = 0 Reorder the terms: 10 + 2x + -1(5 + x)(x + -5) = 0 Reorder the terms: 10 + 2x + -1(5 + x)(-5 + x) = 0 Multiply (5 + x) * (-5 + x) 10 + 2x + -1(5(-5 + x) + x(-5 + x)) = 0 10 + 2x + -1((-5 * 5 + x * 5) + x(-5 + x)) = 0 10 + 2x + -1((-25 + 5x) + x(-5 + x)) = 0 10 + 2x + -1(-25 + 5x + (-5 * x + x * x)) = 0 10 + 2x + -1(-25 + 5x + (-5x + x2)) = 0 Combine like terms: 5x + -5x = 0 10 + 2x + -1(-25 + 0 + x2) = 0 10 + 2x + -1(-25 + x2) = 0 10 + 2x + (-25 * -1 + x2 * -1) = 0 10 + 2x + (25 + -1x2) = 0 Reorder the terms: 10 + 25 + 2x + -1x2 = 0 Combine like terms: 10 + 25 = 35 35 + 2x + -1x2 = 0 Solving 35 + 2x + -1x2 = 0 Solving for variable 'x'. Factor a trinomial. (7 + -1x)(5 + x) = 0Subproblem 1
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Subproblem 2
Set the factor '(5 + x)' equal to zero and attempt to solve: Simplifying 5 + x = 0 Solving 5 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + x = 0 + -5 x = 0 + -5 Combine like terms: 0 + -5 = -5 x = -5 Simplifying x = -5Solution
x = {7, -5}
| -5r-2r=-15-8r+3+7 | | 4x-5=4x+9 | | -3w+8(w-4)=-2 | | 7-2b=19 | | 75=10x-5 | | 1+b=-18-4 | | 27+3x=111 | | -13m+7m=19-73 | | 5x+11=12x-10 | | 10x-2-6x=3y-2+y | | 3x+15+9x+21=180 | | -11x-20=10+40 | | 6y+12=3t+14 | | 6(v+4)-4v=4 | | 14s+2.00=20s+1.50 | | 15Z-32=13 | | -9=-5+t | | x=3+2i | | 14s+2=20s+150 | | -9=5+t | | 8x-7=6x+23 | | 2(x-3)=2*x | | 2w-6w=56 | | 5x+6+6x+5=50 | | -3(h+5)+2=4(h+6) | | 4a-4a^2=0 | | -88-12X=7-2x-6 | | R+20=50 | | -x^4-2x^2+1=0 | | 11+4p=4+3p | | 5-9n+5n=27-82 | | 11Z-17=105 |